AD, Volume 20, n° 4, 1995 - Full Issue - Journal System, (Africa Development, 1995)
Contents Introduction Ayesha Imam ....................... 5 Gender Analysis: The Stunted Discourse in Kenya's Historiography Hanningtoń Ochwada ....................... 11 L'intérêt de l'analyse du genre dans la relation économique entre la femme rurale et son environnement: le cas de Niadiène en Moyenne Casamance Aminata Sow ................................ 29 Les femmes chefs de famille à Dakar Codou Bop .................................. 51 Better life for Rural Women Programme: An Agenda for Positive Change? Udegbe I. Bola .............................69 Gender Relations, Demographic Change and the Prospects for Sustainable Development in Africa Babatunde A. Ahonsi ....................... 85 Relations de genre et relations conjugales Jeanne Nanitelamio ........................... 115 Book Reviews Les familles dakaroises face à la crise by Ph. Antoine Abdourahmane Ndiaye ........................ 133 African Women Liberation: A Man's Perspective by P.N. Wachege Kitula King'ei ..................................... 137 African Women Liberation: A Man's Perspective by P.N. Wachege Kitula King'ei ...................................... 139 Bullies in Uniform: Military Misrule in Nigeria Paul Tiyambe Železa ............................. 143 Publications Received and Acquired ............... 153